2012
DOI: 10.1158/1541-7786.mcr-12-0168
|View full text |Cite
|
Sign up to set email alerts
|

Alkylation Sensitivity Screens Reveal a Conserved Cross-species Functionome

Abstract: To identify genes that contribute to chemotherapy resistance in glioblastoma, we conducted a synthetic lethal screen in a chemotherapy-resistant glioblastoma derived cell line with the clinical alkylator temozolomide (TMZ) and an siRNA library tailored towards “druggable” targets. Select DNA repair genes in the screen were validated independently, confirming the DNA glycosylases UNG and MYH as well as MPG to be involved in the response to high dose TMZ. The involvement of UNG and MYH is likely the result of a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 58 publications
4
49
1
Order By: Relevance
“…These findings are consistent with a role for UBE3B in the cellular response to mitochondrial oxidative stress, because it was shown that TMZ treatment triggers a rapid onset of ROS (29). Similarly, it was shown that the Caenorhabditis elegans ortholog of UBE3B, oxi-1, is required for protein degradation via the UPS, especially under oxidative stress conditions and that deletion of the mouse Ube3b gene led to reduced viability and brain size (25).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…These findings are consistent with a role for UBE3B in the cellular response to mitochondrial oxidative stress, because it was shown that TMZ treatment triggers a rapid onset of ROS (29). Similarly, it was shown that the Caenorhabditis elegans ortholog of UBE3B, oxi-1, is required for protein degradation via the UPS, especially under oxidative stress conditions and that deletion of the mouse Ube3b gene led to reduced viability and brain size (25).…”
supporting
confidence: 81%
“…In a recent synthetic lethal screen done by our laboratory using an siRNA library, the chemotherapy agent temozolomide (TMZ), and a glioblastoma multiforme cell line, we found that knockdown (KD) of UBE3B sensitized cells to TMZ treatment (29). These findings are consistent with a role for UBE3B in the cellular response to mitochondrial oxidative stress, because it was shown that TMZ treatment triggers a rapid onset of ROS (29).…”
supporting
confidence: 69%
“…Accumulating evidence from numerous studies suggests that acquired treatment resistance following TMZ administration is multifactorial and rooted in transcriptional, metabolomic, genomic, and epigenomic changes that lead to this phenotype (60)(61)(62)(63)(64)(65)(66)(67).…”
Section: Temozolamide and Lgg Progressionmentioning
confidence: 99%
“…MMS Sensitivity of the mag1⌬tpa1⌬ Double Mutant Strain Is Not Due to Defective Protein Translation-Increased sensitivity to the alkylation agent MMS has also been reported to arise when a deficiency of proteins involved in the BER pathway is combined in the protein modification pathway (52). In other words, if Tpa1 were involved in the regulation of protein synthesis, then the mag1⌬tpa1⌬ double mutant would show increased sensitivity to MMS.…”
Section: Tpa1mentioning
confidence: 99%
“…We also included a strain deficient in Stp22 in the study as a positive control. It has been reported that stp22⌬ cells are sensitive to these antibiotics because it is a component of the endosomal sorting complexes required for transport (ESCRT) complex that is involved in ubiquitin-dependent sorting of proteins into the endosome (52). As shown in Fig.…”
Section: Tpa1mentioning
confidence: 99%